2015
DOI: 10.1038/ki.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype standardization for drug-induced kidney disease

Abstract: Drug induced kidney disease is a frequent cause of renal dysfunction; however, there are no standards to identify and characterize the spectrum of these disorders. We convened a panel of international, adult and pediatric, nephrologists and pharmacists to develop standardized phenotypes for drug induced kidney disease as part of the phenotype standardization project initiated by the International Serious Adverse Events Consortium. We propose four phenotypes of drug induced kidney disease based on clinical pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
118
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 8 publications
0
118
0
5
Order By: Relevance
“…Drug‐induced hepatotoxicity was diagnosed according to the criteria of drug‐induced liver disorders in which aspartate aminotransferase (AST) and/or alanine aminotransferase (ALT) levels more than three times the upper limit of normal were considered to have hepatotoxicity . Chronic kidney injury was diagnosed as persistence of hematuria, proteinuria, or/and casts for more than 90 days . As you can see in Figure , the diagram of study enrollment is shown.…”
Section: Methodsmentioning
confidence: 99%
“…Drug‐induced hepatotoxicity was diagnosed according to the criteria of drug‐induced liver disorders in which aspartate aminotransferase (AST) and/or alanine aminotransferase (ALT) levels more than three times the upper limit of normal were considered to have hepatotoxicity . Chronic kidney injury was diagnosed as persistence of hematuria, proteinuria, or/and casts for more than 90 days . As you can see in Figure , the diagram of study enrollment is shown.…”
Section: Methodsmentioning
confidence: 99%
“…Because NGAL and tobramycin use a similar transport receptor (megalin), these results suggest that other biomarkers may also be predictive of disordered pharmacokinetics for other medications depending on their respective transport physiologies. Finally, a recent combined adult and pediatric international multicenter initiative has been aimed at assessing genetic predisposition to medication-associated AKI by using genome-wide association studies 22 .…”
Section: What Does the Future Hold?mentioning
confidence: 99%
“…A panel of international pediatric and adult nephrologists and pharmacists developed a standardized description of the phenotype for drug-associated kidney disease in hospitalized patients [36]. The four general categories include AKI, glomerular disorders, nephrolithiasis and tubular dysfunction, and underlying mechanisms can either be dose-dependent or dose-independent (as in acute interstitial nephritis) [36].…”
Section: Who Develops Aki?mentioning
confidence: 99%
“…The four general categories include AKI, glomerular disorders, nephrolithiasis and tubular dysfunction, and underlying mechanisms can either be dose-dependent or dose-independent (as in acute interstitial nephritis) [36]. The authors concede that multi-drug exposures and concurrent AKI risk factors make the use of these criteria challenging.…”
Section: Who Develops Aki?mentioning
confidence: 99%